Estimación de intervalos biológicos de referencia del hemograma en niños y jóvenes de 2 a 18 años utilizando los métodos percentil empírico, bootstrap, Harrell & Davis, y el estimador robusto de horn (2017)
ABSTRACT: Clinical laboratory results should be interpreted according to biological intervals obtained from reference individuals. Intra- and inter-variability of biological magnitudes and of other factors such as nutrition and geographical origin, play an important role. These values are usually calculated with statistical tools that are not tested for statistical assumptions, or without considering the required sample size for validity. Methods: Percentile, bootstrap, Harrell & Davis’, and Horn’s robust methods were used in this study to estimate biological reference intervals of 20 parameters of the hemogram from 842 young people aged between 2 and 18 years. The classification of pediatric populations by age and sex recommended by Soldin et al. (2003) was considered. Also, the intervals proposed by such authors were compared with those contained in this study for leukocytes, red blood cells, hemoglobin, and platelets in order to determine if there were substantial changes in the populations studied, and to establish which of the methods evaluated would provide an interval for the clinician to determine the hematological status of the population studied. Results and conclusions: In most cases, bootstrap and Horn’s robust methods provided wider intervals than those obtained with empirical percentile and Harrell & Davis’ methods. The lower limit calculated with the robust estimator was far below the median value, and the bootstrap method produced the higher upper limit. Marked differences were observed after comparing each interval with those proposed by Soldin et al., even when intra-individual variability was low, as in the case of hemoglobin. These results confirmed the need for each laboratory to estimate its own biological intervals using standardized protocols.